ETHNOLOGICAL ANALYSIS: MIGRATION OF UZBEKISTAN STUDENTS TO THE REPUBLIC OF KOREA - Rahimberdiyev Sardorbek Bekmurod ugli (Web of Journals Publishing, 2025)
The main objective of this study is to identify Uzbek students migrating to the Republic of Korea for education and the factors that attract them. In the process of research, a literature review was used to collect information about the education systems of the two countries, the achievements made in the education system, the achievements and shortcomings of corruption-free education. The result shows that corruption-free education is the most influential factor that influenced their decision. Students also decide to choose their specialty and study in the language they want. Scholarships awarded to students based on their ability in their major and any opportunities available will influence their decision to choose an educational destination.
Keywords: Public Education, Anti-corruption policy, Educational (academic) corruption.